Pain, Depression, and Posttraumatic Stress Disorder Following Major Extremity Trauma Among United States Military Serving in Iraq and Afghanistan: Results From the Military Extremity Trauma and Amputation/Limb Salvage Study. Issue 3 (March 2021) - Castillo, Renan C.; Carlini, Anthony R.; Doukas, William C.; Hayda, Roman A.; Frisch, Harold M.; Andersen, Romney C.; D'Alleyrand, Jean-Claude; Mazurek, Michael T.; Ficke, James R.; Keeling, John J.; Pasquina, Paul F.; Wain, Harold J.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: Assess the burden and co-occurrence of pain, depression, and posttraumatic stress disorder (PTSD) among service members who sustained a major limb injury, and examine whether these conditions are associated with functional outcomes. Design: A retrospective cohort study. Setting: Four U.S. military treatment facilities: Walter Reed Army Medical Center, National Naval Medical Center, Brooke Army Medical Center, and Naval Medical Center San Diego. Patients/Participants: Four hundred twenty-nine United States service members who sustained a major limb injury while serving in Afghanistan or Iraq met eligibility criteria upon review of their medical records. Intervention: Not applicable. Main Outcome Measurements: Outcomes assessed were: function using the short musculoskeletal functional assessment; PTSD using the PTSD Checklist and diagnostic and statistical manual criteria; pain using the chronic pain grade scale. Results: Military extremity trauma and amputation/limb salvage patients without pain, depression, or PTSD, were, on average, about one minimally clinically important difference (MCID) from age- and gender-adjusted population norms. In contrast, patients with low levels of pain and no depression or PTSD were, on average, one to 2 MCIDs from population norms. Military extremity trauma and amputation/limb salvage patients with either greater levels of pain, and who experience PTSD, depression, or both, were 4 to 6 MCIDs from population norms. Regression analyses adjusting for injury type (upper or lower limb, salvage or amputation, and unilateral or bilateral), age, time to interview, military rank, presence of a major upper limb injury, social support, presence of mild traumatic brain injury/concussion, and combat experiences showed that higher levels of pain, depression, and PTSD were associated with lower one-year functional outcomes. Conclusions: Major limb trauma sustained in the military results in significant long-term pain and PTSD. Overall, the results are consistent with the hypothesis that pain, depression, and PTSD are associated with disability in this population. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.